Contract law - McKendrick, Ewan (Oxford ; New York : Hart Publishing Bloomsbury Publishing Plc, 2023)
"Contract Law is a bestselling core textbook written by the leading expert in the field. Its comprehensive coverage and incisive analysis gives students the edge in coursework and exams. Unrivalled for its clarity of explanation, it expertly inks contractual judicial legal theory, practice to practical contractual issues to provide students with a deep understand of contract law. Fully updated with the latest developments in the law, it makes an idea core text for students at undergraduate and postgraduate level"--
Agreement : clearing the ground -- Offer and acceptance -- Certainty and agreement mistakes -- Consideration and form -- Intention to create legal relations --Third part rights -- What is a term? -- The sources of contractual terms -- The classification of contractual terms -- Exclusion clauses -- A duty to disclose material facts? -- Misrepresentation --Common mistake and frustration -- Illegality -- Capacity -- Duress, undue influence, and inequality of bargaining power -- Unfair terms in consumer contracts -- Performance and discharge of the contract -- Breach of contract -- Damages for breach of contract -- Obtaining an adequate remedy.
Includes bibliographical references (pages 476-482) and index.
Keywords: Contracts -- England; Casebooks (Law)